Time-restricted feeding protects against cisplatin-induced acute kidney injury in mice - Kyu Won Jang; Young Suk Kim; Min Jeong Kim; Seo Rin Kim; Dong Won Lee; Soo Bong Lee; Il Young Kim (The Korean Society of Nephrology, 2024)
Background Time-restricted feeding (TRF), devoid of calorie restriction, is acknowledged for promoting metabolic health and mitigating various chronic metabolic diseases. While TRF exhibits widespread benefits across multiple tissues, there is limited exploration into its impact on kidney function. In this study, our aim was to investigate the potential ameliorative effects of TRF on kidney damage in a mouse model of cisplatin-induced acute kidney injury (AKI). Methods Cisplatin-induced AKI was induced through intraperitoneal injection of cisplatin into C57BL/6 male mice. Mice undergoing TRF were provided unrestricted access to standard chow daily but were confined to an 8-hour feeding window during the dark cycle for 2 weeks before cisplatin injection. The mice were categorized into four groups: control, TRF, cisplatin, and TRF + cisplatin. Results The tubular damage score and serum creatinine levels were significantly lower in the TRF + cisplatin group compared to the cisplatin group. The TRF + cisplatin group exhibited reduced expression of phosphorylated nuclear factor kappa B, inflammatory cytokines, and F4/80-positive macrophages compared to the cisplatin group. Furthermore, oxidative stress markers for DNA, protein, and lipid were markedly decreased in the TRF + cisplatin group compared to the cisplatin group. TUNEL-positive tubular cells, cleaved caspase-3 expression, and the Bax/Bcl-2 ratio in the TRF + cisplatin group were lower than those in the cisplatin group. Conclusion TRF, without calorie restriction, effectively mitigated kidney damage by suppressing inflammatory reactions, oxidative stress, and tubular apoptosis in a mouse model of cisplatin-induced AKI. TRF holds promise as a novel dietary intervention for preventing cisplatin-induced AKI.